Spectrophotometric method for determination of aluminium content in water and beverage samples employing flow-batch sequential injection system - Khanhuathon,Y. (Academic Press Inc., 2015)
© 2015 Elsevier Inc. A sensitive, precise and reliable flow-batch method for the determination of aluminium (Al) was developed using a sequential injection-monosegmented flow system incorporating a mixing chamber unit. Eriochrome cyanine R (ECR) was used as a chromogenic reagent in the presence of N,N-dodecyltrimethylammonium bromide (DTAB). The Al-ECR complex at pH 6 gave a maximum absorption at 584nm. In-line single standard calibration and a standard addition procedure were developed employing the monosegmented flow technique. Under the optimum conditions, a linear calibration graph in the range of 0.0075-0.625mgL-1 Al was obtained with limits of detection and quantitation of 0.0020 and 0.0070mgL-1, respectively. Relative standard deviations were 0.8 and 1.3% for 0.010 and 0.025mgL-1 Al (n=11), respectively. A sample throughput of 24h-1 using an in-line standard calibration approach and 6h-1 using four standard addition levels was achieved. The developed system was successfully applied to water samples and beverage samples. The results agreed well with those obtained from the ICP-AES method. Good recoveries between 85 and 104% were obtained.